Enhanced thermal conductivity and mechanical properties of polyurethane composites with the introduction of thermally annealed carbon nanotubes - Ha, Yu-Mi; Lim, Daun; Lee, Sol Yi; Kim, Jaewoo; Kim, Jin Hee; Kim, Yoong Ahm; Jung, Yong Chae (한국고분자학회, 2017)
Here we report a significant enhancement in the physical properties of polyurethane composites by incorporating thermally annealed carbon nanotubes. The highly pure and crystalline carbon nanotubes were prepared by thermally annealing the catalytically grown thin multi-walled carbon nanotubes (t- MWNTs) at 2,300 A degrees C using a graphite furnace in argon. The results of thermally annealing the catalytically as-grown carbon nanotubes in argon at high temperature were the effective removal of metallic impurities, the decrease in both the interlayer spacing and R-value, and the development of straight, crystalline layers. Moreover, the observation of the strong optical signal from the thermally annealed carbon indicates the possibility of growing small diameter innermost tubes below 1 nm within the hollow core of t-MWNTs. Finally, the introduction of the thermally annealed carbon nanotubes allowed us to make more mechanically strong and more thermally conductive polyurethane nanocomposites.